Speaking up: using OSTEs to understand how medical students address professionalism lapses. Issue 1 (1st January 2016) - Tucker, Constance R.; Choby, Beth A.; Moore, Andrew; Parker, Robert Scott; Zambetti, Benjamin R.; Naids, Sarah; Scott, Jillian; Loome, Jennifer; Gaffney, Sierra
Abstract : Background: Objective-structured teaching encounters (OSTEs) are used across many disciplines to assess teaching ability. The OSTE detailed in this paper assesses 191 fourth-year medical students' (M4) ability to identify and address lapses in professionalism based on Association of American Medical Colleges' professionalism competencies. The research questions addressed are How frequently do M4s address professionalism lapses observed during an OSTE? What factors influence whether M4s provide feedback when they observe professionalism lapses in an OSTE? Methods: Standardized patients (SPs) and standardized learners (SLs) were recruited and trained to participate in a standardized encounter with specific cognitive, social, and behavioral errors, including professionalism lapses. M4s viewed this encounter and then offered feedback to the SL, while remotely observed by faculty. Post-encounter, the SL and faculty completed identical checklists to assess both teaching readiness and ability to address professionalism concerns. Results: An analysis of frequencies showed that six of the Association of American Medical Colleges' nine professional competencies were addressed in the checklist and/or discussed in the focus group. Analysis of transcribed debriefing sessions confirmed that M4s did not consistently address professionalism lapses by their peers. Conclusions: In focus groups, M4s indicated that, while they noticed professionalism issues, they were uncomfortable discussing them with the SLs. Findings of the current study suggest how medical educators might support learners' ability to address lapses in professionalism as well as topics for future research.